2020
DOI: 10.7759/cureus.7519
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Medical College Admission Test Scores and Self-assessment Materials with the United States Medical Licensing Examination Step 1 Performance

Abstract: Candidates' performance on the United States Medical Licensing Examination (USMLE) Step 1 examination had been correlated with the Medical College Admission Test (MCAT). However, in 2015, a new MCAT format was released and its correlation with Step 1 remains to be fully analyzed. Preparation for Step 1 typically involves purchasing and perusing practice tests from the National Board of Medical Examiners (NBME) and UWorld; however, their predictive value to performance on Step 1 remains to be ascertained, espec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 18 publications
(24 reference statements)
0
10
0
Order By: Relevance
“…According to the research shown above, there was a significant positive association between EMREE and your The results of the study demonstrated a positive correlation between the resident's performance throughout the residency program's first year and the pre-entry exam [18]. Similarly, Saguil, Dong, and others discovered that the preentry exam is the best predictor of future success [19].…”
Section: Discussionmentioning
confidence: 74%
“…According to the research shown above, there was a significant positive association between EMREE and your The results of the study demonstrated a positive correlation between the resident's performance throughout the residency program's first year and the pre-entry exam [18]. Similarly, Saguil, Dong, and others discovered that the preentry exam is the best predictor of future success [19].…”
Section: Discussionmentioning
confidence: 74%
“…60 In another study, the subjective rating that a COMLEX Qbank was helpful was associated with lower COMLEX 1 scores in the unadjusted analysis but not in the fully adjusted models. 61 Studies that examined performance on self-assessments found that Qbank percent correct scores 49,72 and practice exam scores were correlated with Step 1 scores. 49,51,60 A greater number of practice tests completed was associated with higher Step 1 scores in 1 study 49 but not in another study, 50 and reported use (vs nonuse) of a practice test was not associated with Step 1 scores in a third study.…”
Section: Resultsmentioning
confidence: 99%
“…The UWorld database does not contain questions actually given at licensing examinations which may be seen as a limitation. However, UWorld questions have been deemed as most closely resembling USMLE® ( Andyryka, 2014 ) and UWorld scores are good predictors of USMLE Step 1 scores ( Seal et al, 2020 , Giordano et al, 2016 ). Moreover, the fact that original USMLE® questions are kept secret limits their educational impact and makes comparison of UWorld with the equally open Swedish questions relevant.…”
Section: Discussionmentioning
confidence: 99%
“…From the Swedish national database of previous licensing examinations ( Karolinska Institutet, 2020 ) we retrieved all 34 examinations held between 2010 and fall 2018. 1 As we were denied access to the USMLE®-database 2 we chose a commercial question bank (UWorld for USMLE® step 3 ( UWorld for USMLE step 3., 2020 ), commonly used by students to prepare for USMLE® exams ( Bhatnagar et al, 2019 , Seal et al, 2020 ) and previously described as most representative of questions seen on USMLE® ( Andyryka, 2014 ). We confined ourselves to the following NCDs: coronary heart disease (CHD), chronic obstructive pulmonary disease (COPD), diabetes, hypertension, and stroke.…”
Section: Methodsmentioning
confidence: 99%